Prognostic factors in thyroid carcinomas: a 17-year outcome study - Makazlieva, Tanja; Vaskova, Olivija; Stojanoski, Sinisha; Manevska, Nevena; Miladinova, Daniela; Velikj Stefanovska, Vesna (Archives of Endocrinology and Metabolism, 2019)
The aim of our study was to evaluate the survival rate of all thyroid carcinomas (TCs) diagnosed in the 1999-2015 period in the Republic of North Macedonia and to analyze the prognostic influence of several characteristics on development of distant metastases, as well as to analyze the prognostic effect of seven clinical and constitutional features on mortality.
Keywords: thyroid carcinomas; survival rate; prognostic factors